Paper No P17: A Spherically Shaped Display for Use as an Artificial Iris. (September 2013) - De Smet, J.; De Backer, P.; Islamaj, E.; Joshi, P.; Cuypers, D.; De Smet, H.
Abstract: An artificial iris utilizing a spherically shaped liquid crystal cell filled with a guest–host mixture is presented. By patterning the cell in concentric circles, the opening and closing of an iris can be mimicked. A practical implementation of the artificial iris is described and remaining problems are listed.